1990
DOI: 10.1001/jama.1990.03450220059023
|View full text |Cite
|
Sign up to set email alerts
|

Tubal Sterilization and the Long-term Risk of Hysterectomy

Abstract: To assess the effect of tubal sterilization on the risk of hysterectomy, we studied 7414 women aged 20 to 49 years who had had a tubal sterilization at a health maintenance organization between January 1, 1968, and December 31, 1983. Compared with a population-based cohort of nonsterilized women, women sterilized while 20 to 29 years old were 3.4 times more likely to have had a subsequent hysterectomy (95% confidence interval, 2.4 to 4.7). Adjustment for the effects of potential confounders with a subset of 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
0
18
1
3
Order By: Relevance
“…11,[24][25][26][27][28][29] However, in our study there was no difference in the risk of undergoing hysterectomy between those women who had had tubal sterilization and those who had not-a finding confirmed by a more recent US study. 30 Prior pill and IUD use was associated with a lower likelihood of hysterectomy, but the relation was not statistically significant. However, the likelihood of hysterectomy was increased among those who experienced side effects and stopped using the IUD, probably because of complications arising from IUD use as well as inherent physiologic conditions.…”
Section: Discussionmentioning
confidence: 88%
“…11,[24][25][26][27][28][29] However, in our study there was no difference in the risk of undergoing hysterectomy between those women who had had tubal sterilization and those who had not-a finding confirmed by a more recent US study. 30 Prior pill and IUD use was associated with a lower likelihood of hysterectomy, but the relation was not statistically significant. However, the likelihood of hysterectomy was increased among those who experienced side effects and stopped using the IUD, probably because of complications arising from IUD use as well as inherent physiologic conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Stergachis et al [10], using data from the Group Health Cooperative (GHC) of Puget Sound, USA, found that women who had had a TS between ages 20 and 29 years (n = 7414) as well as wives with vasectomized husbands (n = 5323) were both 3.4 times (95% CLs: 2.4-4.7) more likely to have had a subsequent hysterectomy than was the population-based cohort of unsterilized women (n = 25 736). However, TS was not associated with hysterectomy among women who underwent TS at age 30 or older.…”
Section: Studies That Suggest An Increased Riskmentioning
confidence: 99%
“…Thus, the need for hysterectomy for women in the comparison (unsterilized) group who use OCs may be decreased [7,9,10]. In contrast, by discontinuing OCs after TS, the sterilized women may experience more menstrual disturbances than before TS.…”
Section: Potential Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stergachis et al [6] used the records of a health maintenance organization (HMO) to compare 7,414 sterilized women with 25,736 nonsterilized women and with another group of 5,323 wives of vasectomized men. Using crude relative risks (RRs), after matching on age and duration of membership of the HMO, they found a significant overall excess (RR = 1.6) of hysterectomies among sterilized women relative to the larger 'population-based' control group, and also (RR = 1.4) relative to the wives of vasectomized men.…”
Section: Introductionmentioning
confidence: 99%